Extensive Natural Variation in Arabidopsis Seed Mucilage Structure - Voiniciuc, Cătălin; Zimmermann, Eva; Schmidt, Maximilian Heinrich-Wilhelm; Günl, Markus; Fu, Lanbao; North, Helen M.; Usadel, Björn (Frontiers in Plant Science, 2016)
Hydrated Arabidopsis thaliana seeds are coated by a gelatinous layer called mucilage, which is mainly composed of cell wall polysaccharides. Since mucilage is rich in pectin, its architecture can be visualized with the ruthenium red (RR) dye. We screened the seeds of around 280 Arabidopsis natural accessions for variation in mucilage structure, and identified a large number of novel variants that differed from the Col-0 wild-type. Most of the accessions released smaller RR-stained capsules compared to the Col-0 reference. By biochemically characterizing the phenotypes of 25 of these accessions in greater detail, we discovered that distinct changes in polysaccharide structure resulted in gelatinous coatings with a deceptively similar appearance. Monosaccharide composition analysis of total mucilage extracts revealed a remarkable variation (from 50% to 200% of Col-0 levels) in the content of galactose and mannose, which are important subunits of heteromannan. In addition, most of the natural variants had altered Pontamine Fast Scarlet 4B staining of cellulose and significantly reduced birefringence of crystalline structures. This indicates that the production or organization of cellulose may be affected by the presence of different amounts of hemicellulose. Although the accessions described in this study were primarily collected from Western Europe, they form five different phenotypic classes based on the combined results of our experiments. This suggests that polymorphisms at multiple loci are likely responsible for the observed mucilage structure. The transcription of MUCILAGE-RELATED10 (MUCI10), which encodes a key enzyme for galactoglucomannan synthesis, was severely reduced in multiple variants that phenocopied the muci10-1 insertion mutant. Although we could not pinpoint any causal polymorphisms in this gene, constitutive expression of fluorescently-tagged MUCI10 proteins complemented the mucilage defects of a muci10-like accession. This leads us to hypothesize that some accessions might disrupt a transcriptional regulator of MUCI10. Therefore, this collection of publicly-available variants should provide insight into plant cell wall organization and facilitate the discovery of genes that regulate polysaccharide biosynthesis.